Tensile properties of durian skin fibre reinforced plasticized polylactic acid biocomposites - Anuar, Hazleen; Razali, Mohd Syafiq; Saidin, Hafizul Adzim; Badrul Hisham, Ammelia Fazlina; Mohd Apandi, Siti Nur E’zzati; Ali, Fathilah (Deerhill Publishing, 2016)
This research investigates the effects of plasticizer and durian skin fibre (DSF) loading on tensile and morphological properties of polylactic acid (PLA) biocomposites. Epoxidized palm oil (EPO) was added as a plasticizer in this project. The effect of EPO content 0–10 wt% was investigated over the tensile properties of PLA. EPO at 5 wt% was found to provide the highest tensile properties on PLA biocomposite. The plasticized PLA was then investigated for the effect of DSF content by varying the DSF at 1, 3 and 5 wt%. The tensile properties improved by about 7% with 3 wt% DSF. Scanning electron micrograph revealed that a ductile failure was induced in PLA composite with 5 wt% EPO and 3 wt% DSF.